Priming With Intermittent Theta Burst Transcranial Magnetic Stimulation Promotes Spinal Plasticity Induced by Peripheral Patterned Electrical Stimulation - Yamaguchi, Tomofumi; Fujiwara, Toshiyuki; Lin, Su-Chuan; Takahashi, Yoko; Hatori, Kozo; Liu, Meigen; Huang, Ying-Zu (Frontiers in Neuroscience, 2018)
This study explored the effect of corticospinal activity on spinal plasticity by examining the interactions between intermittent theta burst transcranial magnetic stimulation (iTBS) of the motor cortex and peripheral patterned electrical stimulation (PES) of the common peroneal nerve. Healthy volunteers (n = 10) received iTBS to the tibialis anterior (TA) muscle zone of the motor cortex and PES of the common peroneal nerve in three separate sessions: 1) iTBS-before-PES, 2) iTBS-after-PES, and 3) sham iTBS-before-PES. The PES protocol used ten 100-Hz pulses every 2 seconds for 20 minutes. Reciprocal inhibition from the TA to soleus muscle and motor cortical excitability of the TA and soleus muscles were assessed at baseline, before PES, and 0, 15, 30, and 45 minutes after PES. When compared to the other protocols, iTBS-before-PES significantly increased changes in disynaptic reciprocal inhibition for 15 minutes and altered long-loop presynaptic inhibition immediately after PES. Moreover, the iTBS-induced cortical excitability changes in the TA before PES were correlated with the enhancement of disynaptic reciprocal inhibition immediately after PES. These results demonstrate that spinal plasticity can be modified by altering cortical excitability. This study provides insight into the interactions between modulation of corticospinal excitability and spinal reciprocal inhibition, which may help in developing new rehabilitation strategies.